2020
DOI: 10.3390/cancers12030629
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Suppressors in Chronic Lymphocytic Leukemia: From Lost Partners to Active Targets

Abstract: Tumor suppressors play an important role in cancer pathogenesis and in the modulation of resistance to treatments. Loss of function of the proteins encoded by tumor suppressors, through genomic inactivation of the gene, disable all the controls that balance growth, survival, and apoptosis, promoting cancer transformation. Parallel to genetic impairments, tumor suppressor products may also be functionally inactivated in the absence of mutations/deletions upon post-transcriptional and post-translational modifica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 115 publications
0
6
0
1
Order By: Relevance
“…DNA methylation in mammalian cells is limited to CpG regions that usually occur in promoter areas and thereby prevents gene transcription, while gene activation is exerted by its demethylation (Figure 3; Kong et al, 2019). The methylation of the promoter area allows the regulation of differential gene expressions, and may also be involved in chronic lymphoblastic leukemia (CLL) pathogenesis (Andreani et al, 2020). The DNA methyltransferases (DNMTs), such as DNMT1, DNMT3A, DNMT3B, and DNMT3L, can methylate DNA by passing the methyl group into the cytosine pyrimidine base in 5′-CpG-3 dinucleotides (Rajabi et al, 2016).…”
Section: Epigenetic Regulation Mechanismmentioning
confidence: 99%
“…DNA methylation in mammalian cells is limited to CpG regions that usually occur in promoter areas and thereby prevents gene transcription, while gene activation is exerted by its demethylation (Figure 3; Kong et al, 2019). The methylation of the promoter area allows the regulation of differential gene expressions, and may also be involved in chronic lymphoblastic leukemia (CLL) pathogenesis (Andreani et al, 2020). The DNA methyltransferases (DNMTs), such as DNMT1, DNMT3A, DNMT3B, and DNMT3L, can methylate DNA by passing the methyl group into the cytosine pyrimidine base in 5′-CpG-3 dinucleotides (Rajabi et al, 2016).…”
Section: Epigenetic Regulation Mechanismmentioning
confidence: 99%
“…Besides that, it was also found that deletion on chromosome 13 at locus q14 (13q14del) also contributed to better prognosis in patients. This locus contains the coding sequence for miR-15a/16-1 cluster which target TERT suppressor p53 [108,109]. The mechanism is illustrated in Figure 3.…”
Section: Chronic Lymphoid Leukemia (Cll)mentioning
confidence: 99%
“…Chronic lymphocytic leukemia is also characterized by high levels of B-cell lymphoma 2 (BCL-2) protein, which is involved in inactivating apoptosis [14] and allowing CLL cells to evade cell death. Furthermore, loss of function of tumour suppressor genes such as TP53, ataxia telangiectasia mutated (ATM), and other somatic gene mutations (ie, SF3B-1) or complex karyotypes lead to chemotherapy-resistance in CLL [15,16]. A number of clinically approved agents have been developed to target these pathways and proteins, including acalabrutinib (BTK inhibitor), ibrutinib (BTK inhibitor), idelalisib (PI3Kδ inhibitor), obinutuzumab (anti-CD20 antibody), rituximab (anti-CD20 antibody), and venetoclax (BCL-2 inhibitor).…”
Section: First-line Treatment Evolution In the Young Fit Populationmentioning
confidence: 99%